Green marketing strategies applied in Salikneta Farm: Towards global agricultural environment sustainability - Santos, Francia R. (Animo Repository, 2019)
Mother earth's vulnerability to natural calamities was explicated to have been caused by climate change. Green marketing seems to be one of the major activities under corporate social responsibility that serves as a platform for environmental programs of every business organization. Through green marketing practices and by-products, environmental problems such as the impact of global warming could be reduced gradually. The literature shows green marketing to have a crucial role in agribusiness and environment, hence, the green movement is a big challenge around the globe.This study focuses on the assessment of green marketing strategies as applied by the management and personnel of the Agriculture and Veterinary (Agri-Vet) laboratory farm of De La Salle Araneta University (DLSAU), Salikneta San Jose Del Monte, Bulacan. All the green marketing strategies specifically reducing wastes, having less packaging materials, elimination of specific hazardous substances, recycling materials, and environmental risk management proved their vital importance for environmental protection. Findings of the study reveal that all green marketing strategies, albeit, creating real value for the organization and agribusiness environment were observed to have been adopted by the respondents and methods were used but not that exceedingly applied in the farm. Implications of this study determined on farm management emphasize how those green marketing strategies could be fully enforced for a more sustainable agribusiness and global environment.